The PH-dependent activity and the protonophoric mechanism of pyrazinoic acid and its structural analogues - Piedade Neto Guerra Fontes, Fabio Levi, author; Crick, Dean C., advisor; Crans, Debbie C., advisor; Roess, Deborah, committee member; Ross, Eric, committee member (Colorado State University. Libraries, 2019)
Pyrazinamide is an anti tubercle drug used in the standard treatment regimen against Mycobacterium tuberculosis, the cause of tuberculosis infections. The mechanism of action of pyrazinamide requires its enzymatic conversion to pyrazinoate, but the final molecular target of pyrazinoate is controversial. Pyrazinamide also exhibits pH dependent activity in vitro, but the phenomenon was seldom explained by the mechanisms of action proposed in literature. Moreover, pyrazinamide is known to synergize with other anti mycobacterial drugs in vivo but reports of this synergistic activity in vitro are scarce. The work presented here aimed to gain insight on the mechanism of action of pyrazinamide that explains both its activity and the pH dependent behavior in vitro, while seeking to understand the synergism of pyrazinamide in vitro. The results presented here show the pH dependent activity is not caused by pH sensitivity of M. tuberculosis, as the data demonstrates the bacilli are able to maintain pH homeostasis in a pH range between 5.5 and 7.3. Additionally, M. tuberculosis actively replicates in physiologically extreme pH environments (pH 5.5 and pH 8.5), albeit at a slower rate than at neutral pH values. Mycobacterial cultures treated with pyrazinoic acid showed growth inhibition that correlates with the relative concentration of the acid (but not of its conjugated base, pyrazinoate). Treatment with pyrazinoic acid also leads to concentration dependent acidification of the cytoplasm of mycobacterial bacilli and concentration dependent dissipation of the electric potential across the cytosolic membrane. These results led to the conclusion that pyrazinoic acid, but not pyrazinoate, is the active form of pyrazinamide. The mechanism involves the enzymatic conversion of pyrazinamide into pyrazinoate. Pyrazinoate then crosses the cytosolic membrane and is exposed to the acidic environment, where an acid base equilibrium is established with pyrazinoic acid. Pyrazinoic acid crosses the membrane and reaches the cytosol, where the more neutral pH leads to the loss of the proton it carried from the extracellular environment. The acid base equilibrium outside the cell generates a higher relative concentration of pyrazinoic acid as the pH of the environment becomes more acidic, leading to the pH dependent activity of pyrazinamide. The work presented here demonstrates the pH dependence is not replicated by other anti tubercle drugs, such as rifampin, isoniazid or bedaquiline. However, structural analogues of pyrazinoic acid, such as salicylic acid, and a known protonophore, carbonyl cyanide m chlorophenyl hydrazone, mimic the pH dependent growth inhibition of pyrazinoic acid. A model for the pH dependent activity of these compounds was derived, based on chemical assumptions. The model demonstrates that pyrazinoic acid acts as a protonophore, causing the disruption of proton motive force, and that this mechanism is only possible if no other cellular target exists. The synergism of pyrazinoic acid with rifampin and isoniazid in vitro was determined, using the median effect principle, at different pH environments. Additionally, salicylic acid was tested in combination with rifampin or isoniazid to determined if the drug drug interactions of pyrazinoic acid with these drugs was mimicked by its structural analogues, like its mechanism was shown to be. The results indicate pyrazinoic acid behaves additively with both rifampin and isoniazid in vitro, which was seen in salicylic acid as well. The data indicates that the drug drug interactions of pyrazinoic acid are replicated by salicylic acid. Additionally, the results suggest the synergism of pyrazinamide in vivo may originate from some type of host effect that was not present in the in vitro studies conducted.
Keywords: protonophore; pyrazinoic acid; mycobacteria tuberculosis; salicylic acid; pyrazinamide